2008
DOI: 10.1111/j.1360-0443.2008.02335.x
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias training and cue reactivity in cigarette smokers

Abstract: These data are the first to show alterations in attentional bias for smoking-related stimuli following a modified visual probe training procedure. Furthermore, post-training group differences in subjective craving suggest potential clinical utility of training procedures, although these effects may operate only in males. Future research should investigate whether multiple training sessions enhance post-training reductions in craving and cue reactivity, and the longer-term persistence of training effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(154 citation statements)
references
References 37 publications
11
140
0
3
Order By: Relevance
“…Moreover, in one of the studies with smokers, posttraining AB correlated positively with craving to smoke in the attend group, but only among men 11 ; and in one of the studies about alcohol use, the urge to drink and beer consumption in the attend group was greater in the avoid alcohol. 51 In contrast, of the five studies that compared avoid (to drug) and control groups, only one found no differences between groups.…”
Section: Drug Addictionmentioning
confidence: 93%
See 3 more Smart Citations
“…Moreover, in one of the studies with smokers, posttraining AB correlated positively with craving to smoke in the attend group, but only among men 11 ; and in one of the studies about alcohol use, the urge to drink and beer consumption in the attend group was greater in the avoid alcohol. 51 In contrast, of the five studies that compared avoid (to drug) and control groups, only one found no differences between groups.…”
Section: Drug Addictionmentioning
confidence: 93%
“…The fourth and final concern about study methods is training contingencies and follow-up assessments. Some studies found that awareness contingency improved efficiency, 9,11 and their authors suggested that explicit instructions about the purpose of training might affect results if these methods were applied clinically, and that participants should be made aware of experimental contingencies. 9 This systematic review focused on methods and results of studies about ABM using a specific modified visual probe task, which may be a limitation of this study.…”
Section: Some Methodological Issues Of the Studies Undermentioning
confidence: 99%
See 2 more Smart Citations
“…nicotine & tobacco research social networking/engagement (Richardson et al, 2013), cognitive training (Attwood, O'Sullivan, Leonards, Mackintosh, & Munafò, 2008), video messaging (Whittaker et al, 2011), and in situ cue-exposure treatment (Conklin & Tiffany, 2002).…”
Section: Clinical Significance Of Smartphone Systems That Detect Smokmentioning
confidence: 99%